2013
DOI: 10.1371/journal.pone.0084201
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gene-Expression Analysis of the Dental Follicle and Periodontal Ligament in Humans

Abstract: The human dental follicle partially differentiates into the periodontal ligament (PDL), but their biological functions are different. The gene-expression profiles of the dental follicle and PDL were compared using the cDNA microarray technique. Microarray analysis identified 490 genes with a twofold or greater difference in expression, 365 and 125 of which were more abundant in the dental follicle and PDL, respectively. The most strongly expressed genes in the dental follicle were those related to bone develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Thrombospondin-4 is a transmembrane CAM, which was the only upregulated CAMs apart from periostin and thus may have an important role. It has been detected in the PDL (Lee et al, 2013) but its function was mostly studied in the context of cancer, where it promotes cell proliferation and migration (Chen et al, 2019, p. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombospondin-4 is a transmembrane CAM, which was the only upregulated CAMs apart from periostin and thus may have an important role. It has been detected in the PDL (Lee et al, 2013) but its function was mostly studied in the context of cancer, where it promotes cell proliferation and migration (Chen et al, 2019, p. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal dentition was noted in one previous patient with a similarly large deletion of 8q21 (9.8 Mb; chr8: 74362438‐84172022), suggesting that a gene within 8q21 but outside the critical region for the syndrome may be involved in dentition. One gene within this region, STMN2 was recently identified to be upregulated in the periodontal ligament, the connector between the tooth and alveolar jaw bone, compared to the dental follicle [Lee et al, ]. Two other genes within the region involved in bone metabolism, IL7 and PAG1 , were also shown to be expressed in periodontal ligament cells with changes in expression in response to tensile strain [Pinkerton et al, ; Chang et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…This chemokine and its receptor may be involved in the progression of tissue destruction (including bone resorption) during periapical inflammation (45). A recent study found that the gene expression in the dental follicles was related to bone development and remodeling, apoptosis, and chemotaxis (15). This might also suggest that the immune responses of the APC are related to the development and remodeling of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative reverse-transcription polymerase chain reaction (qRT-PCR) was performed using a modified version of a method used in previous studies (14)(15)(16). Diluted cDNA was used as a template for quantitative polymerase chain reaction (qPCR), which was performed using the ABI 7300 Real-Time PCR system (Applied Biosystems, Warrington, UK).…”
Section: Quantitative Reverse-transcription Polymerase Chain Reactionmentioning
confidence: 99%